Usahawan siswa UiTM 2023: Inkubator MASMED Beautypreneur (Facial) - UiTM, MASMED (Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2023)
Menerima dana darpada TEKUN berjumlah RM 5,000.